Sistem Pendukung Keputusan Pemilihan Ketua Klasis Siep Asso Menggunakan SAW - Hence Lumentut; Silviani Esther Rumagit; Smit Rikardi Malingkas (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
The selection of the Head of the Siep Asso Classis is a strategic process in determining leaders who are able to manage church services and organizations effectively. This process often faces obstacles of subjectivity, lack of transparency, and the absence of measurable assessment methods. This research aims to design and build a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to produce objective and systematic decisions. The SAW method is used to calculate the preference score for each candidate based on predetermined and weighted criteria, including leadership, service experience, integrity, communication and commitment. Data was obtained through interviews, questionnaires and documentation studies. System design uses flowcharts and Data Flow Diagrams (DFD), while development is carried out using PHP and MySQL. System testing applies Black Box Testing to ensure functions run as required. The research results show that SAW-based SPK is able to provide candidate recommendations accurately, consistently and transparently. This system helps minimize subjectivity and supports a fairer and more measurable decision-making process.